GREEN SUPPLY CHAIN PRACTICES AND MSME PERFORMANCE IN LAGOS STATE, NIGERIA - Ibrahim, Alfa; Kassah, Virginia; Christy, Zwingina T. (African Journal of Social and Behavioural Sciences, 2025)
The role of sustainable business practices like green supply chain management cannot be overemphasised in a volatile business sphere. This study aims to empirically explore the effect of green supply chain management on the performance of Micro, Small, and Medium Enterprises (MSMEs) operating in Lagos State, a major hub of MSMEs and the commercial centre of Nigeria. The specific objectives include the effects of green procurement and green manufacturing on the Performance of Micro, Small, and Medium Enterprises. The study adopted a survey research design. The population of the study comprised business owners and managers of the 3,235,987 MSMEs in Lagos State, Nigeria, as reported by SMEDAN in 2021. Taro Yamane’s formula (1967) was adopted to obtain a manageable Sample Size of 440, and the reliability of the instrument was analysed using multiple linear regression analysis. Findings revealed that green procurement has a significant effect on the performance of MSMEs in Lagos State, Nigeria; green manufacturing has no significant effect on the performance of MSMEs in Lagos State, Nigeria. The study recommended that Owners and Managers of MSMEs should ensure that quality inspection processes are in place to ensure that every material supplied complies with environmental sustainability. Additionally, owners and managers of MSMEs should improve their production processes through the adoption of eco-friendly machines that produce less sound and vibration.